From Management to Support: A Systematic Bibliometric Review of Cross-Cultural Human Resource Management - Tianji GAO; László ERDEY (Cross-Cultural Management Journal)
Cross-cultural human resource management has become essential for multinational companies. However, the research outputs of this and related fields are still developing. This study utilised CiteSpace to analyse 330 papers on cross-cultural HRM published from 2002 to 2024 in the Web of Science core collection using bibliometric and visualisation methods. Results show an increasing trend of studies in cross-cultural HRM, with American, European, and Asian countries taking the lead. Author, institution, and country co-authorship networks were generated to identify the top productive authors, institutions, and countries, respectively. The journal co-citation network illustrates the distribution of core journals. The document co-citation network reveals the key research. The keywords co-occurrence network explores the research trend and hotspots. References and suggestions for the development of cross-cultural HRM research are provided.